Orm’s Vernacular Latin - Thomas, Carla María (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Abstract: This article argues that Homily 3 on the Annunciation in the Ormulum presents an image of the stella maris epithet for the Virgin Mary in the English vernacular in a way diff erent fr om its native predecessor, the Old English Gospel of Pseudo-Matthew. In bringing this piece of liturgical material to the laity for the fi rst time, Orm was not only drawing on Latin content fr om multiple Continental sources—thus creating a composite text without a clear exemplar—but he was also elevating his vernacular composition by adapting it to the Latin septenary. Thus, Orm’s use of the stella maris, or “sæsterrne,” demonstrates his participation in the dissemination of Marian devotional material to the laity as well as in the attempt to elevate English through Latin form and content, which represents a larger movement in the period. Keywords: Ormulum, sæsterrne, stella maris, septenary, Virgin Mary.